FLAVONOID CONTENT DETERMINATION AND CYTOTOXICITY TEST OF CARRAGEENAN GEL MOUTHWASH - Aprilla F. Rofiqoh; Abu Bakar; Arya Adiningrat; Yulia Rahmad (Universitas Muhammadiyah Semarang, 2025)
Introduction: Mouthwash is an antibiotic-based product that fights bacteria, oral infections, cleans, deodorizes, refreshes the oral cavity, and is an antiseptic. Carrageenan is a class of galactan polysaccharides found as an intercellular matrix substance in red algae or algae from the Rhodophyta class. Carrageenan is also known to contain secondary metabolite compounds, namely flavonoids, alkaloids, triterpenoids, proteins, carbohydrates, and fats. Aim: The aim of the study is to determine flavonoid levels and cytotoxicity assay of carrageenan gel mouthwash. Methods: The samples of this study were carrageenan gel mouthwash and fibroblast cells. The samples used was divided into cell control groups (negative) and carrageenan gel mouthwash groups with concentrations of 0.5%, 1%, 2%, and 4%. Results: Total flavonoid levels in carrageenan gel mouthwash preparations with 4 different concentrations have flavonoid levels with a 0.5% concentration of 45.42%, 1% concentration of 69.77%, 2% concentration of 65.09%, and 4% concentration of 38.97%. The cytotoxicity test showed cell viability of more than 60% at various concentrations. The highest cell viability in the carrageenan hydrogel mouthwash with a concentration of 2% at 80.57%. Conclusion: The carrageenan hydrogel mouthwash that has the highest flavonoid content at a concentration 1% was 69.77% and the carrageenan gel mouthwash was non-toxic to fibroblast cells.